100 The Impact of Dietary Analyzed Ca to P Ratios and Standardized Total Tract Digestible P to Net Energy Ratios on Growth Performance, Bone, and Carcass Characteristics of Pigs. (12th April 2022) - Williams, Hadley; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Goodband, Robert D; Gebhardt, Jordan T; Vier, Carine M; Lu, Ning; Cast, Wayne; Navales, Ron; Spindler, Matthew; Orlando, Uislei A; et al.
Abstract: A total of 2, 184 pigs (initially 12.4 kg) were used to evaluate effects of varying analyzed Ca:P ratios at 2 levels of standardized total tract digestible (STTD) P:NE. Pens of pigs (26 pigs/pen) were assigned to 6 dietary treatments in a randomized complete block design with 14 pens/treatment. Diets consisted of 2 levels of STTD P:NE: PIC recommendation (1.8, 1.62, 1.43, 1.25, 1.10, 0.99 g STTD P/Mcal NE from 11-22, 22-40, 40-58, 58-81, 81-104, 104-129 kg, respectively) or 75% of the PIC recommendation, and 3 analyzed Ca:P ratios: 0.90:1, 1.30:1, and 1.75:1. Diets were corn-soybean meal-based and contained phytase (Quantum Blue G, AB Vista, Marlborough, UK; 500 to 210 FTU/kg with release values from 0.13 to 0.07% STTD P). There was a Ca:P×STTD P:NE interaction ( P < 0.05) observed for ADG, G:F and final BW. For ADG and final BW, when feeding 75% of PIC STTD P recommendation, increasing analyzed Ca:P ratio decreased ADG and final BW (linear, P< 0.001). But when feeding at PIC STTD P recommendation, increasing the analyzed Ca:P ratio tended to improve ADG and final BW (linear, P< 0.10). For G:F, when feeding 75% of PIC STTD P recommendation, increasing analyzed Ca:P ratio tended to decrease G:F (linear, P < 0.10), whereas in pigs fed diets that met PIC STTD P recommendations, increasing analyzed Ca:P ratio tended to improve G:F in a quadratic ( P < 0.10) manner. Pigs fed at PIC STTD P recommendations had increased ADG, final BW, and G:F compared with pigs fed 75% of PIC STTD P recommendations ( P < 0.001). In summary, pigs fed at PIC STTD P recommendations had improved overall ADG and G:F compared with pigs fed diets at 75% PIC STTD P recommendations. Additionally, increasing analyzed Ca:P ratio reduced ADG and G:F when STTD P was below PIC recommendations, but had marginal impacts when adequate STTD P was fed.